Perancangan Aplikasi Bahasa Inggris pada Smartphone Berbasis Android - Kurnia, Ulfa Isni; Kurniawansah, Alfi (Universitas Lampung, 2023)
The making of this application is motivated by the problem of the lack of use of smartphones as a medium of learning in the world of education. Where smartphones are more widely used for social media than used for learning media. Learning media on smartphones can be called mobile learning. Mobile learning that will be designed is an English learning application, especially learning tenses and verbs. The purpose of making this final project is to design an Android application whose features are expected to facilitate users in learning tenses and knowing verbs practically on English learning applications. In developing this application using the Unified Modeling Language (UML) model and the Android-based java programming language with the Eclipse Juno Integrated Development Environment (IDE). Produced an English Learning application, especially learning tenses and knowing verbs based on Android which has features to display tenses material, verb search and practice reading, tenses and listening questions practically in learning English so that it can help users learn more easily, effectively and efficiently and can learn anywhere and anytime. It is hoped that this application can provide convenience for users in learning English, especially tenses and verbs, so that users can learn anywhere and anytime and maximize the use of smartphones as learning media in the world of education.